2022
DOI: 10.1186/s13195-021-00948-8
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and sex modulate fatty acid metabolism in a prospective observational study of cognitive decline

Abstract: Background Fatty acids play prominent roles in brain function as they participate in structural, metabolic and signaling processes. The homeostasis of fatty acids and related pathways is known to be impaired in cognitive decline and dementia, but the relationship between these metabolic disturbances and common risk factors, namely the ɛ4 allele of the apolipoprotein E (ApoE-ɛ4) gene and sex, remains elusive. Methods In order to investigate early al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Many common disorders, such as CVD, cancer, obesity, and Alzheimer's disease (AD), are now understood to be influenced by chronic inflammation. In addition, several prospective studies have shown that participants with higher circulating vitamin B5 have greater odds of cognitive decline 7 and, similarly, that dietary intake of vitamin B5 is linearly associated with Aβ load in several regions of the brain 13 . In addition, some studies have shown that hypertension increases the risk of AD 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many common disorders, such as CVD, cancer, obesity, and Alzheimer's disease (AD), are now understood to be influenced by chronic inflammation. In addition, several prospective studies have shown that participants with higher circulating vitamin B5 have greater odds of cognitive decline 7 and, similarly, that dietary intake of vitamin B5 is linearly associated with Aβ load in several regions of the brain 13 . In addition, some studies have shown that hypertension increases the risk of AD 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A case‐control study also noted that serum vitamin B5 levels were significantly higher in type 2 diabetes mellitus (T2DM) patients with higher body mass index (BMI), which may be associated with IR 11,12 . In addition, in neurodegenerative disease, studies have indicated that circulating levels of vitamin B5 were higher among those participants who had greater odds of cognitive decline over a 12‐year follow‐up 7 . Vitamin B5 intake may be associated with increased cerebral amyloid‐b peptide (Aβ) burden in patients with cognitive impairment 13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, ApoE-containing HDL particles promote cholesterol efflux from extrahepatic cells (10) by ABCA1-and ABCG1-dependent processes, and this process is antagonized by the presence of ApoC-III (9). Finally, it has been shown that cognitive decline might be dependent on the ApoE-ε4 genotype and sex through FA metabolism and related metabolic pathways (27).…”
Section: Discussionmentioning
confidence: 99%